Fetus in Fetu at Prof. Dr. R. D. Kandou Hospital: A Rare Case Report - Lampus, Harsali F.; Candy, Candy; Rendy, Leo; Sorongku, Ronald; Saputra, Sabrandi P. (Medical Scope Journal, 2025)
Abstract: Fetus in fetu (FIF) is a rare congenital disorder in which a malformed fetus-like structure is inside the actual body of the fetus. We reported a 3-day old female baby, born through sectio caesaria with a lump on her right abdomen. On physical examination, a rounded mass of 8x8 cm was palpable in the right hypochondrium. CT-scan of the abdomen with contrast revealed a heterogeneous mass of mixed cystic and solid accompanied by calcification in the form of vertebrae and extremities in the upper right abdomen (size ±5,6 x 6 x 6 cm). The mass appeared to be abutting with the liver, gallbladder, pancreas, and right kidney by pressing the intestinal loops to the left. A laparotomy was performed with extensive tumor excision, and a malformed fetus-shaped mass with good differentiation characterized by a hand-like structure, fairly complete toes and skin on its surface was found. The tumor was diagnosed as a FIF since the benchmark for diagnosing FIF was the shape of a fetus-like mass, a mature bone structure with components such as cranium, vertebrae, pelvis, extremities and even fingers as found in this patient. The patient was carried out a 5-day treatment after surgery, and then was referred to the Pediatric Surgery polyclinic for a follow-up on the histopathological result to confirm the diagnosis but the patient did not come for further treatment. Keywords: fetus in fetu; fetal tumor; aberrant monozygotic twinning; CT-scan abdomen